The Effects of Lidocaine on Central Respiratory Neuron Activity and Nociceptive-Related Responses in the Brainstem–Spinal Cord Preparation of the Newborn Rat. (May 2016) - Shakuo, Tomoharu; Lin, Shih-Tien; Onimaru, Hiroshi
Abstract : BACKGROUND: Lidocaine is widely used in the clinical setting as a local anesthetic and antiarrhythmic drug. Although it has been suggested that lidocaine exerts inhibitory effects on the central and peripheral neurons, there are no reports on its effects on central respiratory activity in vertebrates. In this study, we examined the effects of lidocaine on respiratory rhythm generation and nociceptive response in brainstem–spinal cord preparations from the newborn rats. METHODS: Preparations were isolated from Wistar rats (postnatal day 0–3) and superfused with artificial cerebrospinal fluid equilibrated with 95% O2 and 5% CO2, pH 7.4, at 25°C to 26°C. We examined the effects of lidocaine on the fourth cervical ventral root (C4)-inspiratory activity and on the preinspiratory and inspiratory neurons in the rostral medulla. We also examined the effects on the C4/C5 reflex responses induced by ipsilateral C7/C8 dorsal root stimulation, which are thought to be related to the nociceptive response. RESULTS: The application of low doses of lidocaine (10–20 μM) resulted in a slight increase of the C4 burst rate, whereas high doses of lidocaine (100–400 μM) decreased the burst rate in a dose-dependent manner, eventually resulting in the complete cessation of respiratory rhythm. High doses of lidocaine decreased the burst duration and negative slope conductance of preinspiratory neurons, suggesting that lidocaine blocked persistent Na+ current. After the burst generation of the respiratory neurons ceased, depolarizing current stimulation continued to induce action potentials; however, the induction of the spike train was depressed because of strong adaptation. A low dose of lidocaine (20 μM) depressed C4/C5 spinal reflex responses. CONCLUSIONS: Our findings indicate that lidocaine depressed nociception-related responses at lower concentrations than those that induced respiratory depression. Our report provides the basic neuronal mechanisms to support the clinical use of lidocaine, which shows antinociceptive effects with minimal side effects on breathing. Abstract : Published ahead of print March 9, 2016